Outcome of Posterior Fossa Decompression for Chiari Type I Malformation with Syringomyelia - Koirala, Sagar; Bishokarma, Suresh; Gongal, Dinesh Nath; Marsh, Henry Thomas (Nepal Journal of Neuroscience, 2019)
There are various treatment approaches for treating Chiari type I malformation with syringomyelia. Despite various choices, consensus for one particular approach is lacking. The objective of this study is to find out the clinical and radiological outcome of standard posterior fossa decompression incorporating removal of C1 arch with lax duroplasty in such cases.A retrospective study based on data acquired from a single tertiary center were analyzed. All cases who underwent posterior fossa decompression incorporating removal of C1 arch with lax duroplasty over a period of five years were included and their clinical and radiological progress were recorded during OPD follow up at 6 months.Out of 21 cases, occipital headache with nape of neck pain was the predominant complaint accounting to 71% followed by sensory symptoms and motor weakness, 61% and 33% respectively. Pain resolved in 93%, weakness in 71% and sensory symptoms in 69% of the cases. Only one patient developed hydrocephalus requiring shunting. Radiological improvement of syringomyelia were documented in 76.1% of the patients. There was no mortality.Posterior fossa decompression incorporating removal of C1 arch and lax duroplasty is a safe approach with good outcome in patients with Chiari I malformation with syringomyelia.